A comparative study of PdZSM-5, Pdβ, and PdY in hybrid catalysts for syngas to hydrocarbon conversion. Issue 3 (13th January 2015) - Wang, Chun; Ma, Xiangang; Ge, Qingjie; Xu, Hengyong
Abstract : Pd zeolites with large pores and cavities in hybrid catalysts could promote the formation of C4+ hydrocarbons in the syngas to hydrocarbon process. Abstract : The catalytic conversion of syngas into hydrocarbons over hybrid catalysts consisting of a methanol synthesis catalyst and Pd modified zeolites (PdZSM-5, Pdβ, and PdY) was investigated. The results indicate that the intermediate dehydration step of DME in the syngas to hydrocarbon process mainly occurs on the Brønsted acid sites of the Pd zeolite. The large pores and cavities of Pdβ and PdY promote the formation of C4+ hydrocarbons, which are mainly gasoline-type branched hydrocarbons. Moreover, the large pores and cavities provide enough space for the formation of higher aromatics which are the precursor of coke. The blockage of micropores of the Pd zeolites by hydrocarbon-type coke results in the deactivation of the hybrid catalysts.